A Discrete-Time Downsampling FIR Filter for Windowed Integration Samplers. (8th February 2009) - Raviprakash, Karthik; Kulkarni, Mandar; Chen, Xi; Hoyos, Sebastian; Sadler, Brian M.
Abstract : A novel technique to reduce die area on a discrete-timesinc 2 ↓ 2 filter for charge sampling is proposed. An SNR comparison of the conventional and the proposed topology reveals that the new technique saves 25% die area occupied by the sampling capacitors of the filter. The idea is also extended to implement higher downsampling factors, and greater percentage of area is saved as the downsampling factor is increased. The proposed filter also has the topological advantage over previously reported works of allowing the designers to use active integration to charge the capacitance, which is critical in obtaining high linearity.